Bilateral Popliteal Vein Thrombosis, Acute Pulmonary Embolism and Mild COVID-19 - Suwanwongse, Kulachanya (Cureus, 2020)
In 2020, the coronavirus disease 2019 (COVID-19) has become a global health disaster. Patients with COVID-19 have variable clinical features and unpredictable prognoses; the infectious complication may occur in many organs, causing a broad spectrum of symptoms and severity. Pulmonary embolism (PE) is a fatal urgent complication, which may occur following a severe infection. While the pathogenesis of PE in COVID-19 remains uncertain, it has mainly occurred in patients with severe disease. PE, as an initial presentation of COVID-19 in a patient with mild diseases, is rare and understudied. Here, we describe a young woman with mild COVID-19 illness and no significant risk factors for PE, except obesity, but had developed bilateral popliteal vein thrombosis and submassive PE. Our case emphasizes that thrombotic complications can occur in any COVID-19 patients regardless of the disease severity, questioning the role of preventive anticoagulants in mild COVID-19 cases with certain risk factors.